Long-term obesity promotes alterations in diastolic function induced by reduction of phospholamban phosphorylation at serine-16 without affecting calcium handling - Leopoldo, Ana Paula Lima; Leopoldo, André Soares; Silva, Danielle Cristina Tomaz da [UNESP]; Nascimento, André Ferreira do [UNESP]; Campos, Dijon Henrique Salomé de [UNESP]; Luvizotto, Renata de Azevedo Melo [UNESP]; Deus, Adriana Fernandes de [UNESP]; Freire, Paula Paccielli [UNESP]; Medeiros, Alessandra; Okoshi, Katashi [UNESP]; Cicogna, Antônio Carlos [UNESP] (American Physiological Society, 2014)
Few studies have evaluated the relationship between the duration of obesity, cardiac function, and the proteins involved in myocardial calcium (Ca2+) handling. We hypothesized that long-term obesity promotes cardiac dysfunction due to a reduction of expression and/or phosphorylation of myocardial Ca2+-handling proteins. Thirty-day-old male Wistar rats were distributed into two groups (n = 10 each): control (C; standard diet) and obese (Ob; high-fat diet) for 30 wk. Morphological and histological analyses were assessed. Left ventricular cardiac function was assessed in vivo by echocardiographic evaluation and in vitro by papillary muscle. Cardiac protein expression of sarcoplasmic reticulum (SR) Ca2+-ATPase (SERCA2a), calsequestrin, L-type Ca2+ channel, and phospholamban (PLB), as well as PLB serine-16 phosphorylation (pPLB Ser(16)) and PLB threonine-17 phosphorylation (pPLB Thr(17)) were determined by Western blot. The adiposity index was higher (82%) in Ob rats than in C rats. Obesity promoted cardiac hypertrophy without alterations in interstitial collagen levels. Ob rats had increased endocardial and midwall fractional shortening, posterior wall shortening velocity, and A-wave compared with C rats. Cardiac index, early-to-late diastolic mitral inflow ratio, and isovolumetric relaxation time were lower in Ob than in C. The Ob muscles developed similar baseline data and myocardial responsiveness to increased extracellular Ca2+. Obesity caused a reduction in cardiac pPLB Ser(16) and the pPLB Ser(16)/PLB ratio in Ob rats. Long-term obesity promotes alterations in diastolic function, most likely due to the reduction of pPLB Ser(16), but does not impair the myocardial Ca2+ entry and recapture to SR.
Keywords: High-fat diet; Obesity; Cardiac dysfunction; Ca2+-handling proteins; PLB serine-16 phosphorylation